Digitalisasi Sebagai Solusi untuk Mengurangi Korupsi di Sektor Pelayanan Publik - Evi Apriani; Prabu Kemal Manaf; Vivi Riska Ramadani (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
Corruption is a structural problem that undermines government governance and weakens public trust. To address this issue, the use of information technology has emerged as a promising solution to enhance transparency and accountability in the public sector. This study aims to analyze the role of technology in preventing and detecting corruption through the implementation of digital systems such as e-government, e-budgeting, and e-procurement. Using a normative juridical and conceptual approach, this study shows that digitalization can reduce corruption opportunities and strengthen both internal oversight and public participation. However, the success of technology implementation depends greatly on the integrity of implementers, supportive regulations, and the readiness of digital infrastructure. This research emphasizes that the integration of technology with the principles of good governance is a strategic step toward building a clean, efficient, and responsive government.